A community for students.
Here's the question you clicked on:
 0 viewing
anonymous
 one year ago
Given that f(x) = −x + 4 and g(x) = −2x − 3, solve for f(g(x)) when x = 2.
anonymous
 one year ago
Given that f(x) = −x + 4 and g(x) = −2x − 3, solve for f(g(x)) when x = 2.

This Question is Closed

netlopes1
 one year ago
Best ResponseYou've already chosen the best response.1Do you know what's composite function?

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0First calculate g(x)

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0g(2) = 2(2)  3 g(2) = 4 3 = 7 g(2) = 7

netlopes1
 one year ago
Best ResponseYou've already chosen the best response.1\[f(x) = x+4 \quad and \quad g(x)=2x3. \quad f(g(x))=(2x3)+4 \rightarrow\]

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0Now go in to calculate f(x) which would be taken from the answer from g(2) f(7) = (7) + 4 f(7) = 11 f(g(x)) = 11

netlopes1
 one year ago
Best ResponseYou've already chosen the best response.1Or...\[f(g(x))=2x+7 \rightarrow f(g(2))=2.2+7 \rightarrow f(g(2))=11. \]

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0Yeah you could do whichever way is easier ! :)
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.